Postero-Lateral Elbow Dislocation With Ipsilateral Radius And Ulna Fracture: A Case Report - Sreejith Thampy J; Arun H.S; Sagar V (Journal of Clinical and Biomedical Sciences)
Elbow dislocation with ipsilateral diaphyseal fracture of both radius and ulna is a rare injury. How-ever, elbow dislocation with either radius or ulna diaphyseal fracture is commonly reported. We report an uncommon injury of a 33 years old male who had his elbow dislocation with ipsilateral both bones forearm fracture. Elbow dislocation was reduced and fracture both bones were fixed with low contact dynamic com-